2005
DOI: 10.1142/s1005386705000398
|View full text |Cite
|
Sign up to set email alerts
|

A Characterization of Finite Simple Groups by the Degrees of Vertices of Their Prime Graphs

Abstract: If G is a finite group, we define its prime graph Γ(G) as follows. The vertices of Γ(G) are the primes dividing the order of G and two distinct vertices p, q are joined by an edge, denoted by p~q, if there is an element in G of order pq. Assume [Formula: see text] with primes p1<p2<⋯<pk and natural numbers αi. For p∈π(G), let the degree of p be deg (p)=|{q∈π(G)|q~p}|, and D(G):=( deg (p1), deg (p2),…, deg (pk)). In this paper, we prove that if G is a finite group such that D(G)=D(M) and |G|=|M|, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 10 publications
3
38
0
Order By: Relevance
“…we have K = 1 and G ~ A 106 , This complet es the proof of lemma, which concludes the theorem. 13,12,11,10,9,6,5,4,3,1).…”
Section: Od-characterizable Of the Alternating Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…we have K = 1 and G ~ A 106 , This complet es the proof of lemma, which concludes the theorem. 13,12,11,10,9,6,5,4,3,1).…”
Section: Od-characterizable Of the Alternating Groupsmentioning
confidence: 99%
“…Given a finite group G. denote by Soe( G) the socle of G which is the subgroup generated by the set of all minimal normal In a series of articles (Ref. to [1,3,4,5,6,7,8]), it was shown that many finite almost simple groups arc OD-characterizable, which are included in the following proposition.…”
Section: Introductionmentioning
confidence: 99%
“…[7,10] The simple groups S 6 (3) and O 7 (3) are 2-fold ODcharacterizable, while the automorphism groups Aut(S 6 (3)) and Aut(O 7 (3)) are 6-fold OD-characterizable.…”
Section: Remarkmentioning
confidence: 99%
“…[7][8][9][10][15][16][17][18] 1) ), it has been shown that many finite almost simple groups are OD-characterizable or k-fold ODcharacterizable for certain k 2. We point out some of these results.…”
mentioning
confidence: 99%
See 1 more Smart Citation